Edukasi Kesehatan Teknik Menyusui Menggunakan Media Video dan Media Leaflet terhadap Pencegahan Puting Lecet pada Ibu Postpartum - Marlina, Yani; Widiasih, Restuning; Maryati, Ida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the comparison of health education on breastfeeding techniques using video media with leaflets on the prevention of sore nipples in postpartum mothers. The research method used was quasi-experimental with a two-group pre-test-posttest design. The research results show a comparison of knowledge and skills in leaflet media and video media after education, namely that there is no significant difference in understanding with a p-value of 0.301. Still, there is a substantial difference in skills with a p-value of 0.008; video media health education influences skills. Postpartum mothers should use breastfeeding techniques because they attract more attention and provide auditory and visual stimuli simultaneously to maximize results. In conclusion, video media health education can be used to improve the skills of postpartum mothers so that video media can be an alternative for delivering information to postpartum mothers. Keywords: Health Education, Postpartum Mothers, Laeflet Media, Video Media